The Interaction of Pseudomonas fluorescens and Red Onion Filtrate on the Growth and Yield of Cucumbers (Cucumis sativus L.) - Syafaatul Uyun; Yuliani Yuliani (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2026)
This study aims to evaluate the interaction and effects of Pseudomonas fluorescens and red onion filtrate as a natural plant growth regulator (PGR) on the growth and yield of cucumber (Cucumis sativus L.). The experiment used a two-factor factorial randomized block design with three replications. The first factor was P. fluorescens concentration (0%, 1%, and 2% v/v from a 108 CFU/mL stock), and the second factor was red onion filtrate concentration (0%, 25%, 50%, and 75% w/v). Data were analyzed using two-way ANOVA followed by Duncan’s Multiple Range Test (DMRT) at α = 5%. The results revealed that both single factors and their interactions significantly affected all observed parameters. The combination of 2% P. fluorescens and 75% red onion filtrate (P3M4) produced the highest vegetative characteristics, resulting in a plant height of 223.63 cm and 64.67 leaves at 35 DAP. However, for generative parameters, the application of 2% P. fluorescens combined with 50% red onion filtrate (P3M3) showed no statistically significant difference from the higher concentration in accelerating flowering time (18.00 days) and increasing fruit weight (393.17 g). In conclusion, the synergistic application of P. fluorescens and red onion filtrate significantly enhances both vegetative and generative performance of cucumber. For production efficiency, the P3M3 formulation is recommended for practical field applications.